Study on Relationship Between Family Cohesion and Adaptability, and Quality of Life of Caregivers of Children With ASD - Lei, Xianmei (Social Welfare: Interdisciplinary Approach, 2018)
The present study aimed at exploring the status of family cohesion, adaptability, and quality of life of caregivers of children with ASD, as well as the relationship between family cohesion and adaptability, and quality of life. One hundred and sixty-three caregivers of children with ASD from Sichuan province in China were investigated by the Chinese version of Family Adaptability and Cohesion Scale and Beach Center Family Quality of Life Scale. The results showed that: (1) Caregivers of children with ASD had higher level of family cohesion, lower level of adaptability, and medium level of quality of family life; (2) Family cohesion and quality of life were significantly correlated, and adaptability and quality of life were also significantly correlated; (3) Family cohesion and adaptability had a positive impact on quality of family life.
Keywords: caregivers of children with ASD; family cohesion; family adaptability; quality of family life